All-cause admissions following a first ever exacerbation-related hospitalisation in COPD. Issue 1 (3rd January 2023) - Waeijen-Smit, Kiki; Jacobsen, Peter A.; Houben-Wilke, Sarah; Simons, Sami O.; Franssen, Frits M.E.; Spruit, Martijn A.; Pedersen, Christian T.; Kragholm, Kristian H.; Weinreich, Ulla M.
Background: Hospital admissions are important contributors to the overall burden of chronic obstructive pulmonary disease (COPD). Understanding the patterns and causes of hospital admissions will help to identify targets for preventive interventions. This study aimed to determine the 5-year all-cause hospital admission trajectories of patients with COPD following their first ever exacerbation-related hospitalisation. Methods: Patients with COPD were identified from the Danish national registries. Patients experiencing their first ever exacerbation-related hospitalisation, defined as the index event, between 2000 and 2014 were included. All-cause hospital admissions were examined during a subsequent 5-year follow-up period, and categorised using the International Classification of Diseases, 10th revision. Results: In total, 82 964 patients with COPD were included. The mean±sd age was 72±10 years and 48% were male. Comorbidities were present in 58%, and 65% of the patients collected inhalation medication ≤6 months prior to the index event. In total, 337 066 all-cause hospital admissions were identified, resulting in a 5-year admission rate of 82%. Most admissions were due to nonrespiratory causes (59%), amongst which cardiac events were most common (19%). Conclusion: Hospital admissions following a first exacerbation-related hospitalisation are common; nonrespiratory events constitute the majority of admissions. Besides the respiratory causes, treatment targeting the nonrespiratory causes of hospital admission should be considered to effectively decrease the burden of hospitalisation in COPD. Nonrespiratory events are the predominant cause of hospital admission in patients with COPD following their first ever exacerbation-related hospitalisation. These findings challenge the current global post-exacerbation management goals. https://bit.ly/3AkC4QN